1999
DOI: 10.1111/j.1528-1157.1999.tb00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Outcome, and Prognostic Factors of Infantile Spasms and Lennox‐Gastaut Syndrome

Abstract: Summary: Purpose: To analyze the occurrence, outcome, and prognostic factors of infantile spasms (IS) and the LennoxGastaut syndrome (LGS) in a defined population.Methods: All children treated because of IS and LGS in the Department of Pediatrics, University of Oulu, from January 1, 1976, until December 31, 1993, who came from the primary catchment area of the hospital were included. Detailed information concerning their individual pre-, peri-, and postnatal medical histories and medical and laboratory examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
0
11

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 16 publications
6
94
0
11
Order By: Relevance
“…[17] Studies show that 27% of patients with WS evolve to Lennox-Gastaut syndrome (LGS), and that 40% of patients with LGS had WS. [18] This evolution of WS to LGS was not evident in our study, since the follow-up period of patients was rather short, and we had few patients.…”
Section: Discussionmentioning
confidence: 61%
“…[17] Studies show that 27% of patients with WS evolve to Lennox-Gastaut syndrome (LGS), and that 40% of patients with LGS had WS. [18] This evolution of WS to LGS was not evident in our study, since the follow-up period of patients was rather short, and we had few patients.…”
Section: Discussionmentioning
confidence: 61%
“…dentro de los rangos reportados y la etiología fue variada, entre las que destacaron las causas prenatales, tales como las malformaciones cerebrales, Esclerosis Tuberosa, Síndrome de Down y las causas perinatales tal como se ha reportado previamente (10,11,29,30). Se encontró una mayor frecuencia de causalidad secundaria en comparación posiblemente por el mayor acceso de esta población a las pruebas diagnósticas.…”
Section: Discussionunclassified
“…At follow-up of at least 10 years, 5-13% of individuals were in remission and 8% were not mentally retarded. Patients with cryptogenic LGS had a better cognitive outcome compared with patients who had symptomatic LGS [38], but another study reported no difference between the groups [39]. …”
Section: Catastrophic Epilepsies Of Childhoodmentioning
confidence: 95%
“…LGS is often (in 13-65% of cases), and in cases of symptomatic etiology in particular, a continuation of West syndrome [36,38,39]. However, as shown in a communitybased study, prenatal or perinatal abnormalities are not necessarily in correlation with the severity of epilepsy [40].…”
Section: Catastrophic Epilepsies Of Childhoodmentioning
confidence: 96%